Indium antimonide nanowires arrays for promising thermoelectric converters - Gorokh, G. G.; Obukhov, I. A.; Lozovenko, A. A. (Technology and design in electronic equipment, 2015)
The authors have theoretically substantiated the possibility to create promising thermoelectric converters based on quantum wires. The calculations have shown that the use of quantum wires with lateral dimensions smaller than quantum confinement values and high concentration and mobility of electrons, can lead to a substantial cooling of one of the contacts up to tens of degrees and to the heating of the other. The technological methods of manufacturing of indium antimonide nanowires arrays with high aspect ratio of the nanowire diameters to their length in the modified nanoporous anodic alumina matrixes were developed and tested. The microstructure and composition of the formed nanostructures were investigated. The electron microscopy allowed establishing that within each pore nanowires are formed with diameters of 35 nm and a length of 35 microns (equal to the matrix thickness). The electron probe x-ray microanalysis has shown that the atomic ratio of indium and antimony in the semiconductor nanostructures amounted to 38.26% and 61.74%, respectively. The current-voltage measurement between the upper and lower contacts of Cu/InSb/Cu structure (1 mm2) has shown that at 2.82 V negative voltage at the emitter contact, current density is 129.8 A/cм2, and the collector contact is heated up to 75 degrees during 150 sec. Thus, the experimental results confirmed the theoretical findings that the quantum wire systems can be used to create thermoelectric devices, which can be widely applied in electronics, in particular, for cooling integrated circuits (processors), thermal controlling of the electrical circuits by changing voltage value.